Do Warm-Up Strategies Impact the Jumping Performance of Young Female Volleyball Players? - Sannicandro, Italo; Armiento, Luigi; Trotta, Nicola; D'Onofrio, Rosario; Arben, Kaçurri; Agron, Kasa (Physical Education Theory and Methodology, 2026)
Objectives. The aim of this study was to assess whether a warm-up routine incorporating plyometric exercises promotes greater improvements in jumping performance, power output, and neuromuscular responsiveness compared with warm-up strategies commonly used in volleyball practice. Materials and Methods. Twenty-four sub-elite female volleyball players (age: 16.3 ± 0.6 years; body mass: 58.7 ± 3.8 kg; height: 165.6 ± 6.8 cm) from a regional club performed three different warm-up protocols, each lasting 20 minutes: traditional warm-up (TWU), neuromuscular warm-up (NWU), and isometric warm-up (IWU). To minimize fatigue effects, three experimental sessions were conducted with 48-hour intervals. Following each warm-up protocol, participants were randomly assessed using the Squat Jump (SJ), Countermovement Jump (CMJ), Standing Long Jump (SLJ), Squat Jump–Block Jump (SJ–BJ), Repeated Countermovement Jump (RCMJ), and Drop Jump (DJ) tests. Results. Jump performance outcomes demonstrated significantly higher values (p < 0.001) following the NWU protocol. Compared with IWU, TWU resulted in higher performance values in SLJ, SJ–BJ, RCMJ, and shorter ground contact time during the DJ test. Conclusions. Neuromuscular warm-up appears to be particularly effective in sports requiring explosive, high-speed actions, as it may directly enhance training quality and jumping performance during competition. The findings indicate that post-activation performance enhancement (PAPE) can be observed in Under-17 female volleyball players when appropriate warm-up exercises are applied. This study provides practical insights into warm-up strategies for youth volleyball clubs with limited access to resistance training equipment.